Prospects and Precision at the Large Hadron Collider at 14 TeV - de Florian, D; Moch, S; Montagna, G; Piccinini, F; Colferai, D (Colle di Galileo, 2015)
The Workshop gathered world experts in precision predictions in QCD and in the electroweak theory for physics at the LHC. Both discovery and precision physics, as well as their interaction, were addressed. Areas where theoretical improvement is needed were clearly identified in view of the forthcoming Run II of the LHC. Workshop activity opened with the fifth edition of the HP2 conference, bringing together the leading world experts in precision Standard Model calculations. After a central week of lectures addressed to young fellows, the last few days of the workshop hosted a topical meeting on the precision measurement of W boson mass at the LHC, attended by experimentalists and theorists directly involved in the subject.